Maternal knowledge and family support for child food insecurity among households with stunting in young children - Desmon Wirawati; Siti Julaeha; Endang Sri Rahayu (Malahayati International Journal of Nursing and Health Science, 2024)
Bakcground: Stunting is a common health issue. In poor nations, particularly Indonesia, stunting is a long-term problem with chronic malnutrition that results in growth abnormalities in children, where the child's height is lower or shorter (stunted) than the average for their age.Purpose: To determine the relationship between maternal knowledge and family support for child food insecurity among households with stunting in young children.Method: Cross sectional research methodology is being used in this quantitative investigation. 110 toddlers from the Bojongnangka Tangerang Community Health Center's service region served as the study's population of interest. Simple random sampling is the sampling method employed. The measurements taken include the toddler's height and the answers to a questionnaire that the toddler's parents completed. SPSS 20 was used for data analysis. The Mann Whitney test was used to do univariate and bivariate analysis after the data had been gathered.Results: With a p value of 0.041, there is a significant correlation between the occurrence of staining and knowledge. Parental education (P=0.267), family skills (P=0.438), family attitudes (P=0.838), family emotional support (P=0.521), family informational support (P=0.707), and family appreciation support (P=0.872) do not significantly correlate with the prevalence of stunting.Conclusion: The prevalence of stunting in the Bojongnangka Tangerang Community Health Center is significantly correlated with knowledge.